Dietary choline regulates antibacterial activity, inflammatory response and barrier function in the gills of grass carp (Ctenopharyngodon idella). (May 2016) - Zhao, Hua-Fu; Jiang, Wei-Dan; Liu, Yang; Jiang, Jun; Wu, Pei; Kuang, Sheng-Yao; Tang, Ling; Tang, Wu-Neng; Zhang, Yong-An; Zhou, Xiao-Qiu; Feng, Lin
Abstract: An 8-week feeding trial was conducted to determine the effects of graded levels of choline (197–1795 mg/kg) on antibacterial properties, inflammatory status and barrier function in the gills of grass carp. The results showed that optimal dietary choline supplementation significantly improved lysozyme and acid phosphatase activities, complement component 3 (C3) content, and the liver expressed antimicrobial peptide 2 and Hepcidin mRNA levels in the gills of fish ( P < 0.05). In addition, appropriate dietary choline significantly decreased the oxidative damage, which might be partly due to increase copper, zinc superoxide dismutase (Cu/Zn-SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione- S -transferase (GST) and glutathione reductase (GR) activities and increased glutathione content in the gills of fish ( P < 0.05). Moreover, appropriate dietary choline significantly up-regulated the mRNA levels of interleukin 10 and transforming growth factor β1, Zonula occludens 1, Occludin, Claudin-b, c, 3 and 12, inhibitor of κBα, target of rapamycin, Cu/Zn-SOD, CAT, GR, GPx, GST and NF-E2-related factor 2 in the gills of fish ( P < 0.05). Conversely, appropriate dietary choline significantly down-regulated the mRNA levels of pro-inflammatory cytokines, tumor necrosis factor α, interleukin 8, interferon γ, interleukin 1β, and related signaling factors, nuclear factor kappa B p65, IκB kinase β, IκB kinase γ, myosin light chain kinase and Kelch-like-ECH-associated protein 1a (Keap1a) in the gills of fish ( P < 0.05). However, choline did not have a significant effect on the mRNA levels of IκB kinase α, Claudin-15 and Keap1b in the gills of fish. Collectively, appropriate dietary choline levels improved gill antibacterial properties and relative gene expression levels of tight junction proteins, and decreased inflammatory status, as well as up-regulated the mRNA levels of related signaling molecules in the gills of fish. Based on gill C3 content and AHR activity, the dietary choline requirements for young grass carp (266.5–787.1 g) were estimated to be 1191.0 and 1555.0 mg/kg diet, respectively. Highlights: Choline supplementation improved the antibacterial properties of fish gill. Choline supplementation decreased inflammation of fish gill. Choline supplementation improved the barrier function of fish gill. Choline modulates the signaling molecules: TOR, NF-κB, MLCK, Nrf2.